Suplementação com levedura de Crômio eleva a concentração sérica de Crômio em bovinos - Giometti, José (2011)
This study evaluated the effect of daily chromium supplementation at growing doses on serum Cr levels in cattle. Sixty Nellore heifers 2 to 5 years old were randomly assigned to one of four groups (15 heifers/group) fed non-fertilized Brachiaria decumbens pasture. In the control group (Gc), the heifers received a mineral mixture without Cr. In the other groups, heifers received 0.59, 1.19 or 2.38 mg Cr+3/animal/day, groups G8,5, G17 and G34, respectively. Blood samples were collected on days 0, 30 and 60. Serum concentration of chromium was determined by graphite furnace atomic absorption spectrophotometer. The chromium source used was the chromium yeast. The results do not support any significant difference (p>0.05) among serum chromium levels of heifers in groups Gc, G8,5, G17 and G34 at a same observation day. Only effect of supplementation time was detected in group G34. In this group there was significant increase (p<0,05) in the concentration serum chromium 60 days after the beginning of the experiment. Concluded Cr yeast can be used as the source of this mineral element for animals and supplementation with 2.38 mg/ cattle/day was the dose that most increased the serum concentration of Cr in Nellore cattle during the experimental period.